(untitled) (Al-NASR, 2025)
This study explores the scientific themes found in the first Juz of Tafsir Ibn Kathir, highlighting how Qur’ānic verses reflect both spiritual guidance and references to natural phenomena. The introduction explains the Qur’ān’s comprehensive nature, covering spiritual, moral, social, and cosmological subjects, and emphasizes that its scientific allusions reveal its timeless miraculous character. The analysis focuses on selected verses from Surah al-Fātiḥah and Surah al-Baqarah, particularly those addressing prayer, human physiology, natural elements like sulfur stones, and the creation of the heavens and the earth. By comparing Ibn Kathir’s classical interpretations with contemporary scientific findings, the study demonstrates how early exegetes understood cosmological concepts within the framework of their time, and how certain Qur’ānic themes align with modern scientific discoveries. It also distinguishes authentic interpretations from weak or Israelite-influenced narrations. Ultimately, this work aims to show that the Qur’ān provides universal guidance for every era and that its exegetical tradition forms a meaningful bridge between Islamic scholarship and scientific inquiry.